New species of Plutellidae from Iran (Lepidoptera: Yponomeutoidea) - W. Mey (SHILAP)
Three new species of Plutellidae are described from Iran: Baerenschenkia lamasi Mey, sp. n., Deryaxenistis nekrutenkoi Mey, sp. n., and Paraxenistis ammolofon Mey, sp. n. Adults and male and female genitalia are illustrated. The male genitalia of two lectotype specimens, deposited in the Natural History Museum, London were examined and illustrated: Paraxenistis sphenospila Meyrick, 1919 and P. pentaula (Meyrick, 1913). They are provisionally retained in Paraxenstis Meyrick, 1919.